Download presentation

Presentation is loading. Please wait.

Published byScott Powell Modified over 7 years ago

1
**Objective - To solve equations with the variable in both sides.**

2x + 4 = 5x - 17 2x + 4 = 5x - 17 2x + 4 = 5x - 17 -2x x -5x x 4 = 3x - 17 -3x + 4 = -17 21 = 3x -3x = -21 7 = x x = 7

2
**Rules for Solving Equations**

1) Goal: Isolate the variable on one side of the equation. 2) Undo operations with their opposite operation. 3) Always do the same thing to both sides of the equation. 4) Easiest to undo add/subtract before multiply/divide.

3
Solve. 1) 4(x - 2) - 2x = 5(x - 3) 4x x = 5x - 15 2x - 8 = 5x - 15 -2x x -8 = 3x - 15 7 = 3x

4
2) 3(x + 2) - (2x - 4) = - (4x + 1) 3x x + 4 = - 4x - 1 x + 10 = - 4x - 1 + 4x x 5x + 10 = -1 5x = -11 x = =

5
3) 5(m - 6) = [2(m - 7) - 5m] 5m - 30 = [2m m] 5m - 30 = [-3m - 14] 5m - 30 = m + 56 5m - 30 = 12m + 66 -5m m -30 = 7m + 66 -96 = 7m

6
**Solve each equation below.**

a) 3x - 5 = 2x + 12 b) 3x + 8 = 2(x + 4) + x -2x x 3x + 8 = 2x x x - 5 = 12 3x + 8 = 3x + 8 -3x x x = 17 8 = 8 True ! One Solution Identity x = any real number c) 3x + 2 = 2(x - 1) + x 3x + 2 = 2x x 3x + 2 = 3x - 2 -3x x 2 = -2 False ! No Solution

7
**Solve. 4) 4(y - 2) + 6y = 7(y - 8) - 3(10 - y)**

-8 = -86 False Statement No Solution

8
**5) 3(4 + k) - 2(3k + 4) = 5(k - 3) - (8k - 19) **

Solve. 5) 3(4 + k) - 2(3k + 4) = 5(k - 3) - (8k - 19) 12 + 3k - 6k - 8 = 5k k + 19 -3k + 4 = -3k + 4 +3k k 4 = 4 True Statement Infinitely Many Solutions x = any real number

Similar presentations

© 2023 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google